Siły dynamiczne występujące między zębami kół przekładni jednostopniowej o osiach równoległych - NADOLSKI, Władysław (Engineering Transactions, 1971)
Dynamic forces occurring between the teeth of single-stage transmission wheels with parallel axes A discrete model of single-stage tooth transmission with parallel axes is described in this paper with the following assumptions: 1) deformation of shafts and their supports, and of the wheel disks, are very small in comparison with the deformation of the wheels; 2) no collisions occur between the teeth; 3) the graph of the substitute rigidity of the wheels and the graph of the setting of the wheel supports in the tooth rim follows a sinusoidal course. By means of the discrete model, the equations of motion are derived, and subsequently the conditions are given concerning the fluctuation and stability of the solutions of the nonlinear and nonhomogeneous differential equation with variable coefficients. In conclusion, are given relationships on the basis of which the values of the forces between the straight lines can be determined.